The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1957
DOI: 10.1084/jem.106.1.111
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Natural Antibody in the Rejection of Mouse Tumor Cells by the Chick Embryo

Abstract: Cells of the Krebs ascites tumor of mice grow well in the body of the chick embryo until about the 17th day of incubation, when degeneration of the tumor can be seen in tissue sections and viable tumor cells begin to disappear from the internal organs of the embryo. This death of tumor cells follows the appearance in the chick embryo of serum gamma globulins. Among these are antibodies which can agglutinate the tumor cells in vitro, and destroy their viability. These antibodies occur in the bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1961
1961
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…When B77-NRK cells (cells transformed with wild-type RSV) were initially tested as a positive control in the in vivo assay (see below), we found that they grew quite well in vivo at all temperatures up to 38°C but that they did not grow well at 39°C. (This puzzling phenomenon has been reported previously for another tumor cell type by Green and Lorincz [20], who suggested a possible role for natural antibodies in such rejection. As the chicken embryo and aspects of its immune system develop more rapidly at higher temperatures, the poor growth in chicken embryos of B77-NRK cells at 39°C may reflect some sort of immune rejection by the host.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…When B77-NRK cells (cells transformed with wild-type RSV) were initially tested as a positive control in the in vivo assay (see below), we found that they grew quite well in vivo at all temperatures up to 38°C but that they did not grow well at 39°C. (This puzzling phenomenon has been reported previously for another tumor cell type by Green and Lorincz [20], who suggested a possible role for natural antibodies in such rejection. As the chicken embryo and aspects of its immune system develop more rapidly at higher temperatures, the poor growth in chicken embryos of B77-NRK cells at 39°C may reflect some sort of immune rejection by the host.…”
Section: Resultssupporting
confidence: 51%
“…Chicken embryos would appear to provide a nutrient-rich environment, and yet normal cells die rapidly after injection. Immune rejection cannot be implicated, as evidence for an immune response to foreign cells is generally not found in embryos younger than -17 days (20), whereas a decline in the number of normal cells is observed immediately after injection into 11-day-old embryos. Evidence presented here for LA23-NRK cells suggests that the death or growth of cells after injection is dependent on transformation-related properties.…”
Section: Resultsmentioning
confidence: 99%
“…The question arises whether this embryonic tissue can respond to lower levels of glucose because the fed blood sugar did not usually fall below 2.5 g/liter. Work is in progress to determine the threshold glucose concentration necessary to stimulate insulin release from a chick embryonic pancreas because the plasma glucose level of the embryo is below that of the adult I grafts such as the Krebs ascites tumor cells of mice (51) and lymphoid and bone marrow tissues of pigeons (52). However by the 18th d of incubation, allogeneic cells were rejected, indicating that the fate of grafted cells differed in 14-and 18-d embryo hosts (53).…”
Section: Xenotransplantation Of Embryonic Endocrine Pancreas In the Ratmentioning
confidence: 99%
“…The low levels of P observed in burned patients and in some experimental animals subjected t o hemorrhagic shock and to ionizing radiation led naturally to suggestions that P was involved in these processes. These suggestions were based upon the apparent weakness of antibacterial mechanisms in these conditions and the presumed bactericidal activity of P. Similarly, the low levels of P observed in advanced cases of human cancer [51] were correlated with the postulated role of P in the cytotoxic effect of normal serum in vitro [12]. No direct proof that P is directly involved in any of these conditions has been reported, and that is not unexpected in view of its doubtful effect in the bactericidal reaction and lack of effect upon the growth rate or morphology of human cancer cells in tissue culture [51].…”
Section: Biological Activitiesmentioning
confidence: 99%